PHYLOGENETIC TREE ON LERNAEOSIS IN ARWANA FISH (Scleropages jardinii) - Dikry Novel Shatrie; Kurniasih Kurniasih; Wisnu Nurcahyo; Triyanto Triyanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
Arwana Irian fish is one of the endangered species. Some studies on arwana Irian fish found that Lernaeosis attacked arwana Irian fish. Lernaeosis is one of the diseases that cause the high mortality in juvenile fish. The objectives of this research was to find out the species of Lernaea (Copepoda) often attacked arwana Irian fish. Lernaea sp. was collected from Papua and Jakarta (Java). They were fixed in the ethanol absolute solution for DNA sequencing in 28S DNA region with primer 28SF (5’–ACA ACT GTG ATG CCC TTA G–3’); 28SR (5’ TGG TCC GTG TTT CAA GAC G–3’). It was found five different species of Lernaea and one of them was thought as a new species, based on the morphology. However, based on the phylogenetic analysis, they showed three different groups. Lernaea cyprinacea G., L. papuensis, L. devastatrix, and L. lophiara were in one group; L. cyprinacaea and L. oryzophila were in one groups; and the new Lernaea sp. was in the different group.